Analisis Persepsi Pelanggan terhadap Kualitas Jasa dengan Metode Importance Performance Analysis dan Potential Gain Customer Value - Amirah Qulbi Chairissa Al Cholili; Sauptika Kancana (Penerbit Goodwood, 2023)
Purpose: The objectives of the study are first, to know how customers perceive the service quality of Hotel Santika Gresik with an Importance Performance Analysis (IPA) method and second to determine the priority of service quality improvement at Hotel Santika Gresik with the Potential Gain Customer Value (PGCV) method. Methodology: The population in this study is who have used the services at Hotel Santika Gresik and the sample in this study are customers who have used the services at Hotel Santika Gresik in the period November 2020 – April 2022. Determination of the number of samples will be determined with a 95% level of confidence and a margin of error of 10%, the number of samples obtained is 96 respondents. The researcher's decision to increase the sample to 98 respondents so that the sample is better at representing the population and the results are better generalized. The sampling technique used in this study is based on the Non Probabilistic Sampling method using a purposive sampling. Results: The results show that (1) the level of conformity between the interests (importance) of customers and the company's performance on the quality of services provided by Hotel Santika Gresik has an average level of conformity below 100%, which is 95.41%, which means Hotel Santika Gresik still lacking or not fulfilling what is considered important by customers and the service is not fully satisfactory; (2) the priority of improvement on the service quality of Hotel Santika Gresik according to the Importance Performance Analysis (IPA) method is that Hotel Santika Gresik employees serve customers quickly, the behavior of Hotel Santika Gresik employees is able to grow customer trust in them, Hotel Santika Gresik always strives to store proprietary data the customer properly and without error, the equipment owned by Hotel Santika Gresik is complete; (3) the priority of improvement on the service quality of Hotel Santika Gresik with the Potential Gain Customer Value (PGCV) method is that Hotel Santika Gresik employees give individual attention to customers with the highest number of 3.86 and the lobby room at Hotel Santika Gresik is clean and comfortable to get the lowest value is 2.77.